PENGARUH PENGGUNAAN TEKNOLOGI ASISTIF (TRAFFIC LIGHT CARD) TERHADAP KEMANDIRIAN BELAJAR ANAK TUNARUNGU DI SEKOLAH INKLUSI QUANTUM BRAIN - Rahmat, Nur iftitah; Fatimah Azis; Nasir (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to determine the effect of using assistive technology (Traffic Light Card) on the learning independence of deaf children at Quantum Brain Inclusive School. The problem addressed is the low learning independence of deaf children, indicated by their dependence on teacher assistance in understanding instructions and completing learning tasks. This research employed a quantitative approach with a quasi-experimental One Group Pretest-Posttest design. The research subjects were 11 deaf students selected through saturated sampling. Data were collected through questionnaires, observation, and documentation, and analyzed using descriptive and inferential statistics, including normality and hypothesis testing. The results showed that the pretest mean score was 48.45 (low category for all students), while the posttest mean score increased to 73.82 (high category for all students). The Shapiro-Wilk test confirmed that both pretest and posttest data were normally distributed (p > 0.05). The paired sample t-test produced a significance value of 0.000 (p < 0.05), indicating that H0 was rejected and H1 was accepted. It can be concluded that the use of the Traffic Light Card as a simple visual assistive technology is effective in improving the learning independence of deaf children, supported by clear and easily understood visual cues that help students communicate their level of understanding independently. Teachers in inclusive schools are recommended to integrate the Traffic Light Card consistently to enhance students' learning independence, confidence, active participation, decision-making ability, and learning communication.